Race and Immigration in the New Ireland - O'Brien, Sean T.; Edwards, Heather, 1976 December 22-; Ulin, Julieann Veronica (Book collections on Project MUSE., 2013)
Although a number of books have addressed changes in Ireland that are related to immigration, both during and after the Celtic Tiger economic boom and bust, they are often limited by a focus on a single aspect of immigration or on either the Republic of Ireland or Northern Ireland. This book, in contrast, offers a variety of expert perspectives and a comprehensive approach to the social, political, linguistic, cultural, religious, and economic transformations in Ireland that are related to immigration. It includes a wide range of critical voices and approaches to reflect the broad impact of immigration on multiple aspects of Irish society and culture. The contributors address immigration and Irish sports, education systems, language debates, migrant women's issues, human rights policies, and culture both in the Republic and in the North of Ireland. Further, authors offer a framework for considering this new Ireland in relation to earlier colonial contexts, reading intersections between new racism and old sectarianism.